2014
DOI: 10.1002/2013tc003294
|View full text |Cite
|
Sign up to set email alerts
|

Basement shear zones development and shortening kinematics in the Ecrins Massif, Western Alps

Abstract: In the Western Alps, Oligocene shortening affected a highly heterogeneous European crust with Liassic half-grabens inherited from the rifting stage and the finite deformation was strongly partitioned between the rigid basement and the weak Jurassic sediments. In the Ecrins Massif (Oisans, external crystalline massifs), where the half-grabens are best exposed and preserved, compressional structures within the basement have to date never been described in details. This massif was shortened under moderate metamor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 130 publications
1
26
0
Order By: Relevance
“…At the Eocene‐Oligocene boundary, a N‐S to NW‐SE shortening phase is identified: while Dumont et al [] proposed that it affected the entire western ECM, Bellanger et al . [] showed that it may be restricted to the cover in a narrow zone below the Penninic Frontal Thrust. This latter observation is consistent with field evidences further north [ Ceriani and Schmid , ].…”
Section: Geological Setting Of Western Alpsmentioning
confidence: 99%
See 4 more Smart Citations
“…At the Eocene‐Oligocene boundary, a N‐S to NW‐SE shortening phase is identified: while Dumont et al [] proposed that it affected the entire western ECM, Bellanger et al . [] showed that it may be restricted to the cover in a narrow zone below the Penninic Frontal Thrust. This latter observation is consistent with field evidences further north [ Ceriani and Schmid , ].…”
Section: Geological Setting Of Western Alpsmentioning
confidence: 99%
“…The ECM at the Oisans latitude can be divided into several units from west to east: the south Belledonne, Grandes Rousses, and Emparis units (Figure ). Further southeast, two other units are present: the Meije and Combeynot units [ Bellanger et al , , and references therein]. The total amount of shortening at this latitude is about 28 km, including 11.5 km accommodated within the ECM [ Bellahsen et al , ], where the sedimentary cover is not significantly detached over the basement but is rather disharmonically deformed over it.…”
Section: Geological Setting Of Western Alpsmentioning
confidence: 99%
See 3 more Smart Citations